The automated system Steach. Space designed for Programming teaching - Kizyanov, A; Luchaninov, D; Bazhenov, R; Pronin, A; Tabachuk, N; Samorukov, A (Journal of physics. Conference series, 2020)
The research aims at designing and verifying an automated system for online learning in Programming languages. Such systems were designed to provide students' independent theoretical training and exercising within in-person learning and are able to operate on their own. Nginx, Docker, Gunicorn, Django, Python, PostgreSQL, HTML5, and CSS Framework were applied. Testing was held at Sholom-Aleichem Priamursky State University and Pacific National University in the 2019-2020 academic year. Training in C++ and Python was arranged for 30 students for the research efficiency checking. The researchers found out the system used could make Programming learning more efficient. The results showed that it was improved by 30% in an experimental group and by 17% in a control group. The survey data used defined that the participants of the experiment (students, lecturers, experts) appreciated the software solution. The designed system Steach.space has a user-friendly interface, contains modules for developing integrated/built-in courses, providing teaching aids and tests, computer-assisted verification of assignments in Programming, and observing statistics/history on student learning. The software can be used for teaching programming languages, as well as other subject domains.